OC-52 Delivering optimum complex care for in the community: a multidisciplinary approach. (6th June 2017) - Blair, Mitch; Brenner, Maria; Larkin, Philip; Warters, Austin; O'Shea, Miriam
Abstract : Background and aims: Improvements in neonatal and paediatric care mean that more children with complex care needs are surviving into adulthood, placing great challenges on healthcare delivery. This paper will present the preliminary findings the health and social care need of these children at the acute community interface, using traumatic brain injury (TBI) as a trace condition. Methods: Data to explore optimum care for these children were gathered across the European Union (EU) and European Economic Area (EEA) as part of a Horizon 2020 funded project Models of Child Health Appraised (MOCHA), running from 2015 to 2018. Results: A number of key issues in the integration of care for the adolescent with TBI emerged in this study to date. These include: limited inclusion of the young person in the planning of their care, limited engagement of family advocacy groups, significant absence of policies and procedures to support transition to adult services and limited engagement in data collection to understand the experience of the adolescent and their family. Conclusion: The preliminary results suggest that there are limited structures and processes in place to support integrated care delivery to children following a traumatic brain injury across the EU/EEA. Further research is important to explore regional variations and equity of provision of integrated care for this group of children.